2017
DOI: 10.3892/mco.2017.1302
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of osteopontin in acute myeloid leukemia: A meta‑analysis

Abstract: Abstract. Osteopontin (OPN) has been investigated in the field of tumor research for several years. However, the prognostic role of OPN overexpression in acute myeloid leukemia (AML) remains controversial. A meta-analysis of four studies, including a total of 492 patients, was performed to determine the association of OPN with overall survival (OS) in AML patients. The random-effects model of Der Simonian and Laird was used to synthesize data; hazard ratio (HR) with its 95% confidence interval (CI) was used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…However levels (even though significantly upregulated) were low and attempts at protein detection in the model were unreliable. A meta-analysis of several studies indicates that serum osteopontin (OPN) is a marker of poor survival and a potential therapeutic target in AML patients [ 19 ]. We therefore looked for the presence of osteopontin in primary AML patient material.…”
Section: Resultsmentioning
confidence: 99%
“…However levels (even though significantly upregulated) were low and attempts at protein detection in the model were unreliable. A meta-analysis of several studies indicates that serum osteopontin (OPN) is a marker of poor survival and a potential therapeutic target in AML patients [ 19 ]. We therefore looked for the presence of osteopontin in primary AML patient material.…”
Section: Resultsmentioning
confidence: 99%
“…Both β3 integrins belong to the subgroup of RGD binding integrins, i.e., integrins recognizing ligands containing an RGD tripeptide sequence. These integrins are among the most promiscuous and bind to a large number of ligands, including extracellular matrix and soluble vascular ligands [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Important ligands for the β3 integrins are given in Table 1 .…”
Section: The Promiscuity Of β3 Integrin Ligand Bindingmentioning
confidence: 99%
“…Opn is suggested to promote leukemic stem cell quiescence, homing and adhesion to the BM niche through CD44 expression providing protective ME to AML cells and inducing their chemoresistance . Clinically, it has been reported that Opn serum levels inversely correlate with AML prognosis . Our unique ex‐vivo POS system has provided a direct proof for an aberrant function of AML stroma, characterized by a high baseline Opn level which further rises in the presence of AML cells, supporting their proliferation.…”
Section: Discussionmentioning
confidence: 74%
“…As a glycoprotein secreted by osteoblasts and hematopoietic cells, Opn is known to suppress the proliferation of HSCs in vitro , thus regulating their pool. It is mainly expressed in the endosteal bone surface niche and adheres to hematopoietic progenitors through beta‐1 integrin . Constitutive activation of the GM‐CSF receptor has been found to be associated with increased Opn expression, which may lead to dysregulation of normal hematopoiesis, eventually causing AML development via a yet unknown mechanism.…”
Section: Discussionmentioning
confidence: 99%